Dakwah and Awik Awik as Local Wisdom for Forest Preservation In a Muslim Community in West Lombok - Mohammad Liwa Irrubai (Universitas Islam Negeri Mataram, 2018)
This article aims to examine the Awik-awik originating from the local wisdom of a Muslim community in West Lombok and analyzes its interrelation to Islamic propagation (dakwah). This traditional village norms serve as a guide to the people to deal with the forest. Since Islam promotes the preservation of nature, it then aligns itself with such local wisdom. Based on an ethnogrpahic study in Sesaot village and built on the theory of local wisdom, this study attempts to describe the contain, structure and socialization of the awik-awik when it is reshaped from a traditional norm to a written rule agreed upon by the community members. Substantially, the stipulation of the awik-awik could reinforce Islamic doctrines on natural resource maintenance. Moreover, the ways in which the awik-awik is socialized before being implemented resemble the method of religious propagation. This indicat that Awik-awik could be an effective means of Islamic propagation to provide enlightenment to the community because the material arisen from the local wisdom of local communities reflect important Islamic message on the preservation of environment.